1975
DOI: 10.1111/j.1365-2621.1975.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

The protein of intermediate moisture meat stored at tropical temperature

Abstract: Intermediate moisture beef was prepared by desorption (cook-soak-equilibration method) and stored at 38°C. The state of the proteins at processing and during storage was followed by solubility and electrophoretic studies. Two types of protein reactions-breakdown and crosslinking-were found to be going on simultaneously during storage. The crosslinking reactions over-rode the breakdown reactions as storage advanced. The state of the proteins depends on the balance between these reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It suggests that some insolubilisation reactions, hydrolysis and denaturation might have been taking place during this storage period (Garcia et al 1997). Similar, decrease in protein solubility upon storage has been reported in many intermediate moisture meats (Obanu et al 1975;Madovi 1980;Webster et al 1986;Okonkwo et al 1992b;Reyes-Cano et al 1995). However, there was remarkably less degree of decrease here suggesting that crosslinking reactions might be minimal in this type of product.…”
Section: Tba Valuesmentioning
confidence: 43%
See 1 more Smart Citation
“…It suggests that some insolubilisation reactions, hydrolysis and denaturation might have been taking place during this storage period (Garcia et al 1997). Similar, decrease in protein solubility upon storage has been reported in many intermediate moisture meats (Obanu et al 1975;Madovi 1980;Webster et al 1986;Okonkwo et al 1992b;Reyes-Cano et al 1995). However, there was remarkably less degree of decrease here suggesting that crosslinking reactions might be minimal in this type of product.…”
Section: Tba Valuesmentioning
confidence: 43%
“…These carbonyls react with proteins to form premelanoidins which are antioxidants (El-Zeany et al 1973). During storage of intermediate moisture meats, Obanu et al (1975) also observed a decrease in TBA at a later stage. However, TBA values were below 1-2 considered to be the threshold limit for perception of rancidity (Watts 1962).…”
Section: Tba Valuesmentioning
confidence: 98%
“…Three infusion solutions were formulated which would give desired water activity while maintaining the texture and flavour of meat chunks. Most of the workers have used very high levels of glycerol to achieve desired water activity (Brockman, 1973; Obanu et al. , 1975, 1976; Webster et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 1994). This type of pasteurisation or mild heating for killing of vegetative cells during desorption of meat chunks has been also carried by Obanu et al. (1975), Webster et al.…”
Section: Discussionmentioning
confidence: 99%